An inverse opal Cu2Nb34O87 anode for high-performance Li+ storage. Issue 53 (1st June 2020) - Zhu, Xiangzhen; Liang, Guisheng; Fu, Qingfeng; Li, Renjie; Chen, Yongjun; Bi, Yicheng; Pan, Duo; Das, Rajib; Lin, Chunfu; Guo, Zhanhu
Abstract : Inverse opal Cu2 Nb34 O87 with highly-ordered macropores and thin walls is exploited as a practical anode material for high-performance Li + storage. Abstract : Cu2 Nb34 O87 with an inverse opal morphology is fabricated, showing highly-ordered macropores with sizes of ∼170 nm and walls with thicknesses of 20–30 nm. This first-reported Cu2 Nb34 O87 nanomaterial exhibits good Li + -storage properties, including a large capacity, safe operating potential, large initial coulombic efficiency, high rate performance and good cycling stability.